Identification of Components Associated with the Operation of Mutual Aid Groups: A Scoping Review; [Identificación de Componentes Asociados Al Funcionamiento de Los Grupos de Ayuda Mutua: Una Revisión Panorámica] - Rojas-Andrade, R (Universidad Nacional de Colombia, 2023)
This research aims to identify the components associated with the benefits of Mutual Aid Groups (mags). Although they have been singled out by the evidence, specific information on their nuclear components is lacking. Based on the methodological approach of Arksey and O’Malley and the Joanna Briggs Institute, all research studies (Pubmed, Scopus, Scielo, Embase, and Redalyc) and gray literature examining these groups were included. The search was carried out throughout 2022 with the following codes: mutual aid groups; self-help groups. We reviewed 62 papers and 37 were included from a total of 2064 articles. The study shows that the components associated with beneficial results are: active agency, coping strategies, recognition, management of emotions, problem-solving strategies, supportive interaction, trust, self-identity construction, and strengthening of social networks. Thus, it reaffirms that mags are an effective option to address health problems. The application of these components could also contribute to achieve these benefits. © 2023 Universidad Nacional de Colombia. All rights reserved.